Meta-Analysis of the Efficacy and Safety of Ketamine on Postoperative Catheter-Related Bladder Discomfort - Lu, Youyi; Li, Qi; Wang, Yunqiang; Zhou, Zhongbao; Zhang, Dongxu; Bao, Yiping; Wu, Jitao; Cui, Yuanshan (Frontiers in Pharmacology, 2022)
Objectives: We conducted the meta-analysis to demonstrate the efficacy and safety of ketamine on postoperative catheter-related bladder discomfort (CRBD). Methods: A systematic search was performed through PubMed, Embase, and the Cochrane Library to identify all randomized controlled trials that used ketamine in postoperative CRBD. This study was carried out by using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. We used RevMan version 5.3.0. to analyze the data. Results: Five RCTs involving 414 patients were included in the analysis. The incidence and severity of postoperative CRBD were assessed at 0-, 1-, 2-, 6-hour. According to our results of meta-analysis, ketamine reduced the incidence of postoperative CRBD at 2-hour (RR 0.39; 95% CI, 0.21-0.71; P=0.002, I2=40%) and 6-hours (RR 0.29; 95% CI, 0.16-0.50; P＜0.0001, I2=0%) significantly; however, there were no statistical differences at 0-hour (RR 0.81; 95% CI, 0.35-1.88; P=0.62, I2=96%) and 1-hour (RR 0.57; 95% CI, 0.13-2.54; P=0.46, I2=97%). In 2 studies, we compared the incidence of moderate to severe CRBD between groups according to the scaling system (none, mild, moderate and severe), data are presented as numbers. Patients in ketamine group showed a significantly lower severity of CRBD than those in the placebo group at 1-hour (RR 0.09; 95% CI, 0.03-0.31; P=0.0001) and 2-hour (RR 0.06; 95% CI, 0.01-0.44; P=0.005). In contrast, there were no meaningful differences between the two groups in the severity of CRBD at 0-hour (RR 0.18; P=0.84) or 6-hour (RR 0.20; 95% CI, 0.03-1.59; P=0.13). There were no meaningful differences on the rate of adverse events between ketamine group and control group, mainly including postoperative nausea and vomiting (RR 1.24; 95% CI, 0.89-1.72; P=0.21), diplopia (RR 3.00; 95% CI, 0.48-18.67; P=0.24), and hallucination (RR 3.00; 95% CI, 0.32-28.24; P=0.34). Conclusions: Our meta-analysis demonstrated that a sub-hypnotic dose of ketamine administration can reduce the incidence and severity of postoperative CRBD without causing evident side effects. Keywords: ketamine, catheter-related bladder discomfort, randomized controlled trials, meta-analysis,CRBD.